Educational decentralization. Competencies and the supervisory function in countries with a high decentralization degree - Gómez Muñoz, María Nieves (Avances en Supervisión Educativa, 2022)
This article aims, initially, to study the phenomenon of state decentralization, trying to link decentralization with efficiency, drawing conclusions based on technical studies carried out by different experts. We present the RAI index (Regional Authority Index) in order to find the countries with the greatest decentralization in Europe. We are now focus our attention on educational decentralization, finding different models that go from the opposite pole to decentralization (France, which maintains a strongly centralized model), to the totally decentralized model of a federal state (Germany), finding different intermediate states. A general trend is observed in Europe towards educational decentralization, reaching not only territorial decentralization, whether regional, municipal or local, but also moving towards the autonomy of centers where teachers, students and families have decision-making power. The distribution of other competencies in the field of education, and the models and operation of the Educational Inspection, are studied separately and in parallel, as well as figures responsible for School supervision; to end up investigating the concept of High Inspection and similar bodies that may exist in other decentralized countries around us.
Keywords: Decentralization; Educational Inspection; School Supervision; High Inspection